Does a financial crisis affect operating risk? Evidence from Polish listed companies - Kalinowski, Sławomir; Puziak, Marcin (Economics and Business Review, 2018)
In turbulent times of crisis the variability of both EBIT and operating revenueincrease in comparison to a relatively stable post crisis period. The main aim ofthis paper is to investigate this relationship across these two periods. The hypothesis isthat the degree of operating leverage (DOL) is significantly higher during the crisis period(2007-2010) than in the post-crisis period (2011-2015). Additionally the authorschecked whether there were significant differences across defined industries and alsoverified whether all industries had responded in the same way to Financial Crisis as faras DOL is concerned. The main findings are: (a) The Financial Crisis of the years 2008‑2009significantly influenced the DOL of Polish stock companies; (b) There are substantialdifferences of the DOL across industries; (c) The DOL in the case of all industriesinvestigated changed in the same direction when comparing two selected subperiods.